Relationships Between the Microbial Composition and the Geochemistry and Mineralogy of the Cobalt-Bearing Legacy Mine Tailings in Northeastern Ontario - Courchesne, Brittaney; Schindler, Michael; Mykytczuk, Nadia C. S. (Frontiers in Microbiology, 2021)
Mine tailings host dynamic biogeochemical processes that can mobilize a range of elements from the host material and release them into the environment through acidic, neutral, or alkaline mine drainage. We used a combination of mineralogical, geochemical, and microbiological techniques to gain a better understanding of biogeochemical processes within the surficial layers of neutral, cobalt and arsenic-rich tailings material from Cobalt, Ontario, Canada. Tailings material within 30-cm depth profiles from three tailings sites (A, B and C) were characterized for their mineralogical, chemical and microbial community composition. The tailings material at all sites contained (sulf)arsenides (safflorite, arsenopyrite) and arsenates (erythrite and annabergite). Site A contained a higher and lower amount of (sulf)arsenides and arsenates than site B, respectively. Contrary to site A and B, site C depicted a distinct zoning with (sulf)arsenides found in the deeper reduced zone, and arsenates occurring in the shallow oxidized zone. Variations in the abundance of Co+As+Sb+Zn (Co#), Fe (Fe#), total S (S#), and average valence of As indicated differences in the mineralogy of the tailings material. Material with a high Co#, low Fe# and high average valence of As had a higher proportion of secondary arsenate to primary (sulf)arsenide minerals. Microbial community profiling indicated that the tailings were primarily composed of Actinobacteria and Proteobacteria, and known N, S, Fe, methane, and possible As-cycling bacteria. The tailings from sites B and C had a larger abundance of Fe and S-cycling bacteria (e.g. Sulfurifustis and Thiobacillus), which were more abundant at depth, whereas site A had a higher proportion of potential As-cycling and/or -resistant genera (e.g. Methylocystis and Sphingomonas). A multi-variate analysis showed that distinct site-specific groupings occurred for the Co # vs Fe # ,Co# vs S#’s and microbial community structure and that the microbial communities were correlated with depth, S#, Fe#, pH and the average valence of As. The variation in As valence also correlated well with the abundance of N, S, Fe and methane-cycling bacteria. The results of this study provide insights into the interplay between minerals containing the critical element cobalt, arsenic, and microbial community structure in the Cobalt Mining Camp tailings.